2012
DOI: 10.5012/jkcs.2012.56.1.068
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Novel Isopropyl 2-thiazolopyrimidine-6-carboxylate Derivatives

Abstract: ABSTRACT. In the present study, we have synthesized novel Isopropyl 2-(4-substitutedbenzylidene)-5-methyl-3-oxo-7-phenyl-3,7-dihydro-2H-thiazolo[3,2-a]-pyrimidine-6-carboxylate derivatives (6a-j). Elemental analysis, IR, 1 H NMR and mass spectral data elucidated structure of newly synthesized compounds. The newly synthesized compounds were screened for antiinflammatory and anti microbial studies. Their biological activity data of the 10 compounds indicates that two compounds posses potent anti-inflammatory and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Many studies have reported antibacterial activities of derivatives. The structure-activity relationships based on the literature results [27][28][29] indicated that fused pyrimidines, especially thiazolopyrimidine derivatives, have antibacterial activity. The obtained results indicated that the compounds bearing 2-(piperidin-1-yl) 4c and 2-(4-methylpiperidin-1-yl) 4d substituents show the highest sensitivity against Streptococcus equinus and Streptococcus pneumonia, respectively, compared with ceftriaxone and cefazolin as reference drugs, which may be due to the lipophilicity increase of the moiety, which has enhanced the pharmacological activity.…”
Section: Antibacterial Evaluationsmentioning
confidence: 99%
“…Many studies have reported antibacterial activities of derivatives. The structure-activity relationships based on the literature results [27][28][29] indicated that fused pyrimidines, especially thiazolopyrimidine derivatives, have antibacterial activity. The obtained results indicated that the compounds bearing 2-(piperidin-1-yl) 4c and 2-(4-methylpiperidin-1-yl) 4d substituents show the highest sensitivity against Streptococcus equinus and Streptococcus pneumonia, respectively, compared with ceftriaxone and cefazolin as reference drugs, which may be due to the lipophilicity increase of the moiety, which has enhanced the pharmacological activity.…”
Section: Antibacterial Evaluationsmentioning
confidence: 99%
“…These facts together with the powerful biological activity of pyrimidine moiety which is widely used as a key building block for pharmacological agent led us to bind these two interesting moieties and specifically its derivative thiazolopyrimidine hoping to build significant places in medicinal chemistry research .…”
Section: Introductionmentioning
confidence: 99%
“…11 In view of all these observations, we have undertaken the synthesis of some new derivatives of thiazolo [3,2-a]pyrimidines. The traditional methods 7,[12][13][14] to synthesize arylidene derivative involve the use of 1:1 mixture of acetic acid and acetic anhydride in presence of sodium acetate. But this method is not satisfactory with regard to the isolation of the products and also due to the drastic reaction conditions that are employed.…”
Section: Introductionmentioning
confidence: 99%